Absence of IgG antibodies against Schmallenberg virus in ruminant sera (bovine, goat and sheep) collected in Costa Rica between 2012 and 2014. - Villegas-Salas, Marlene (2017)
Schmallenberg virus affects ruminants, which causes significant economic losses. The virus is transmitted through vectors of the genus Culicoides; however, other studies do not rule out the possibility of sexual transmission due to its presence in semen. For this reason, the National Service of Animal Health of Costa Rica (SENASA) imposed restrictions on the import of semen from animals from the European Union in 2013. Consequently, SENASA conducted a study to determine the presence or absence of antibodies against this virus in bovine, ovine and caprine samples. As a result, no antibodies against this virus were detected in the 748 samples tested. It was concluded that Schmallenberg virus was not circulating in Costa Rican ruminants during the tested period.